Energization simulations of a half-wavelength transmission line when subject to three-phase faults—Application to a field test situation - Silva, Eduardo A.; Moreira, Fernando A.; Tavares, Maria C. (Electric power systems research, 2016)
•Three-phase faults may result in high overvoltages and energy stresses in arresters.•There is a region in the line where three-phase faults may lead to arresters failure.•There are differences in the energy stresses in arresters according to the line model used. The purpose of this paper is to supply technical data for the proposed field energization of 500kV transmission lines present in the Brazilian interconnected system, forming a line, henceforth called AC-Link, slightly over a half-wavelength in 60Hz. The purpose of the test is to investigate overvoltages and currents that result from the energization of the AC-Link. This paper shows the results of simulations performed in ATP (Alternative Transients Program) when considering the occurrence of three-phase faults along the AC-Link during energization. The results obtained show that, in certain situations, the overvoltages and energies in the arresters may reach very high values and some specific mitigation procedure should be implemented.